2010
DOI: 10.1667/rr1802.1
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Suppresses Radiation-Induced Apoptosis and TP53 Pathway in Rat Small Intestine

Abstract: The effect of basic fibroblast growth factor (bFGF) was studied in radiation-induced apoptosis in rat jejunal crypt cells. Six-week-old male Wistar rats were administered 4 mg/kg bFGF intraperitoneally 25 h before receiving 8 Gy whole-body X rays. The jejunum was removed for analysis from time 0 to 120 h after irradiation. Villus length in control rats declined steadily until 72 h, while in bFGF-treated rats the villi were longer than in the controls until 48 h. Crypt lengths were similar to villi. bFGF treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…however, it is beyond the scope of this article to explore this background knowledge. subsequently, the listed growth factors are the key factors in wound healing (45,46).…”
Section: Principles Of Wound Healingmentioning
confidence: 99%
“…however, it is beyond the scope of this article to explore this background knowledge. subsequently, the listed growth factors are the key factors in wound healing (45,46).…”
Section: Principles Of Wound Healingmentioning
confidence: 99%
“…As we stated above, we consider the observed Paneth cell activation as a consequent compensatory response to complex alterations in intestinal mucosa that are temporally and functionally associated with further development of symptoms of the acute radiation illness. Therefore, we would expect a shorter time point of Paneth cell activation with increasing irradiation dose> lOGy and vice versa (2,27).…”
Section: Discussionmentioning
confidence: 98%
“…Recent observations indicate that irradiation with doses of -9 Gy does not, per se, cause collapse of crypt/villi structures (2). Taking into consideration the concept of dynamic response of entorocytes to irradiation discussed above, we assumed that enteritis associated with 'the development of acute radiation syndrome reported in this and previous communications is not likely due to the early apoptosis of the proliferating crypt cells, but rather due to irradiation-induced temporal arrest of epithelial cell proliferation, and cell renewal along the cryp/villus axis (20)(21)27). This assumption was corroborated by the appearance of bacteria in crypt lumens of irradiated intestine (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no approved medical countermeasures to alleviate GI syndrome. Several studies have shown that cytokines such as interleukin 11 (IL-11), granulocyte colony-stimulating factor (G-CSF) and basic fibroblast growth factor (b-FGF) could inhibit apoptosis of intestinal epithelial cells and impair radiation-induced intestinal damage [8,9]. However, cytokine treatment is not effective against higher doses of radiation-induced tissue injury.…”
Section: Overview Of Gi Syndromementioning
confidence: 99%